The Ambivalence of the Unveiled: A Feminist Reading on Asghar Farhadi’s Films - Nasehi, Elnaz (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Feminist contribution to the studies of film is rooted in the feminist concerns with the cinematic reproduction of gendered ideologies. Acknowledging the specificity of Iranian society and Iranian cinema, this research endeavors to introduce and theorize “buttressing unconscious” as the neopatriarchal unconscious of Iranian society and discusses “buttressing strategies” as the way it affect representation of female characters narratively and aesthetically on the screen. The main concern of the current research are how buttressing unconscious is inscribed into the screen and it shapes cinematic conscious/unconscious choices of the filmmaker. As buttressing unconscious entails a form of veiling- as a buttress- in order to deactivate the threat of an unveiled/empowered woman, it is inscribed on the screen through the three cinematic functions of veiling; sartorial practices, behavioral codes and sex-segregation. A qualitative method of textual analysis is used to find out how meaning is constructed via various thematic, stylistic, technical and narrative tools in six films directed by Asghar Farhadi, the only Iranian Oscar-winner filmmaker. The analysis reveals that Farhadi’s representation of veiling creates parodies of the conventional propriety in regard to the issue of obligatory hejeb. However, his aesthetic engendered the mise-en-scene and cinematography, and imposes buttressing/veiling gaze on female characters, and while the narrative moves toward the state of reparation and the new state of orders is established, the female empowered characters are buttressed and controlled. Farhadi’s portrayal of patriarchy is pervasive insomuch that he succeeds to address the complex network of dominative mechanisms of patriarchy in the economic, and political levels. However, his desire to move beyond patriarchy fails to reach its object of desire, and reproduces its very core of criticism within in accordance with symbolic culture and the sustainable buttressing unconscious of Iranian society/cinema. Keywords: Iranian Cinema, Feminist Film Studies, Representation of Women, Buttressing Strategy, Buttressing Gaze, Buttressing Unconscious, Neopatriarchal Unconscious, Asghar Farhadi.

ÖZ: Feminizmin film çalışmalarına katkısı, toplumsal cinsiyetlendirilmiş ideolojilerin sinemasal yeniden üretimiyle ilgili feminist kaygılara dayanmaktadır. Bu araştırma, İran toplumunun ve İran sinemasının özgüllüğünü göz önünde bulundurarak, İran toplumunun yeni ataerkil bilinçdışısı olarak sunduğu “payanda stratejisi” üzerine bir kuram inşa etmekte ve bu stratejinin ekranda, kadın karakterlerin anlatımını ve estetik olarak temsilini nasıl etkilediğini tartışmaktadır. Araştırmanın temel ekseni, payanda stratejisinin ekrana nasıl yansıdığı ve film yönetmeninin bilinçli/bilinçdışı sinemasal tercihlerini nasıl şekillendirdiğidir. Başı açık/güçlenmiş kadının yarattığı tehdidi etkisiz hale getirmek için, örtünmeyi bir tür destek gibi sunan payanda stratejisi, ekrana tesettürün üç sinemasal işlevini yansıtmaktadır: örtünme uygulamaları, davranış kodları ve cinsiyet ayrımı. İran’ın Oscar kazanan tek yönetmeni olan Asghar Farhadi’nin yönettiği altı filmde, çeşitli tematik, biçimsel, teknik ve anlatı araçlarıyla anlamın nasıl kurgulandığını ortaya koymak için nitel bir metinsel analiz yöntemi kullanılmıştır. Yapılan analiz, Farhadi’nin tesettür temsillerinin zorunlu tesettür ve geleneksel örtünmeye dair parodiler yarattığını ortaya koymaktadır. Bununla birlikte, Farhadi’nin estetiği, toplumsal cinsiyetlendirilmiş bir mizansen ve sinematografi yaratmakta ve kadın karakterlerine payandalandırılmış/örtünmüş bir bakış empoze etmektedir. Anlatı, çatışmanın çözüldüğü ve yeni bir dengenin oluştuğu aşamaya doğru ilerlerken, kadın karakterler payanda ile desteklenir ve kontrol edilir. Farhadi, ataerkilliğin ekonomik ve siyasal düzeydeki egemen mekanizmalarının karmaşık ağının kapsamlı bir portresini çizmeyi başarır. Bununla birlikte, ataerkilliğin ötesine geçme arzusu, arzu nesnesine ulaşamaz ve Farhadi, eleştirdiklerini, sembolik kültür ve İran toplumunun/sinemasının sürdürülebilir payanda bilinçdışısı doğrultusunda yeniden üretir. Anahtar sözcükler: İran Sineması, Feminist Film Çalışmaları, Kadınların Temsili, Payanda Stratejisi, Payanda Bakışı, Yeni Ataerkil Bilinçdışı, Asghar Farhadi.
Doctor of Philosophy in Communication and Media Studies. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Communication And Media Studies, 2018. Supervisor: Assoc. Prof. Dr. Nurten Kara.
Keywords: Communication and Media; Films--Feminist Reading--Asghar Farhadi Films--Iran; Farhadi, Asghar 1972--Criticism and interpretation; Feminism and motion pictures; Iranian Women in motion pictures; Representation of women in Asghar Farhadi Films; Iranian Cinema; Feminist Film Studies; Representation of Women; Buttressing Strategy; Buttressing Gaze; Buttressing Unconscious; Neopatriarchal Unconscious; Asghar Farhadi